Detection of Group 2a Coronaviruses with Emphasis on Bovine and Wild Ruminant Strains: Virus Isolation and Detection of Antibody, Antigen, and Nucleic Acid - Hasoksuz, Mustafa (SARS- and Other Coronaviruses, 2007)
Group 2a of the Coronaviridae family contains human and animal pathogens that include mouse hepatitis virus, rat coronavirus, human respiratory coronaviruses OC43 and the recently identified HKU1 strain, a newly recognized canine respiratory coronavirus, porcine hemagglutinating encephalomyelitis virus, equine coronavirus, bovine coronavirus (BCoV), and wild-ruminant coronaviruses. The presence of a hemagglutinin-esterase (HE) surface glycoprotein in addition to the viral spike protein is a distinguishing characteristic of most group 2a coronaviruses. BCoV is ubiquitous in cattle worldwide and is an economically significant cause of calf diarrhea, winter dysentery of adult cattle, and respiratory disease in calves and feedlot cattle. We have developed and optimized laboratory diagnostic techniques, including virus isolation in HRT-18 cell cultures, antibody and antigen ELISA, and RT-PCR, for rapid, sensitive, and reliable diagnosis of BCoV and related wild ruminant coronaviruses.